Outcome of Pleural Empyema Treated With Video-Assisted Thoracoscopic Surgery in Patients With Severe Co-Morbidities: An Observational Study - Vu HA; Nguyen NV; Le TD; Nguyen ST; Viet Le A; The Vu A; Van Nguyen B; Van Nguyen B; Thanh Quan N; An NV; Duc Nghiem T (Medical Devices: Evidence and Research)
Hai Anh Vu,1 Nam Van Nguyen,1 Tuan Dinh Le,2 Son Tien Nguyen,2 Anh Viet Le,1 Anh The Vu,3 Ba Van Nguyen,4 Binh Van Nguyen,5 Nam Thanh Quan,6 Nguyen Van An,7 Thuan Duc Nghiem6 1Department of Thoracic Surgery, Military Hospital 103, Vietnam Medical Military University, Hanoi, 10000, Vietnam; 2Department of Rheumatology and Endocrinology, Military Hospital 103, Vietnam Medical Military University, Hanoi, 10000, Vietnam; 3Department of Anesthesia and Pain Medicine, Military Hospital 103, Vietnam Medical Military University, Hanoi, 10000, Vietnam; 4Department of Oncology, Military Hospital 103, Vietnam Medical Military University, Hanoi, 1000, Vietnam; 5AIDS Healthcare Foundation, Hanoi, 10000, Vietnam; 6Department of Otolaryngology, Military Hospital 103, Vietnam Medical Military University, Hanoi, 10000, Vietnam; 7Department of Microbiology Department, Military Hospital 103, Vietnam Medical Military University, Hanoi, 10000, VietnamCorrespondence: Thuan Duc Nghiem, Department of Otolaryngology, Military Hospital 103, Vietnam Medical Military University, 160 Phung Hung Street, Phuc La Ward, ha Dong District, Hanoi, 100000, Vietnam, Email nghiemducthuan@vmmu.edu.vnBackground: Empyema patients with poor physical condition and severe comorbidities face a significant challenge, with difficulties in choosing appropriate treatment methods, limited treatment outcomes, and a high rate of complications and mortality.Objective: To comment on the indications and to evaluate the treatment outcomes of pleural empyema in patients with poor physical condition and severe comorbidities by thoracoscopic surgery.Methods: An observational study on 12 patients treated at the Department of Thoracic Surgery – Military Hospital 103, from January 2017 to December 2022.Results: The mean of age was 63.4 ± 12.4 years old, with a male/female ratio of 5/1. In this study, 83.3% of cases were presented with stage II empyema. The mean Karnofsky score was 50.0 ± 6.1. Some comorbidities contained chronic obstructive pulmonary disease (COPD) (25.0%), spontaneous esophageal perforation (16.7%), liver cancer, cirrhosis, esophageal cancer, end-stage renal failure – chronic dialysis (8.7%). The surgery procedures were efficient with a short duration (65.6 ± 9.4 minutes), low incidence of blood transfusion (8.3%), and lower rate of postoperative complications (surgical wound infection 8.3%). The length of postoperative stay was 16.8 ± 9.9 days. Pleural drainage was removed in 11 out of 12 cases after an average of 60.1 ± 8.5 days, while one patient had their drainage retained due to esophageal cancer. The total recovery rate at the 1-year follow-up was 91.7%.Conclusion: Video-Assisted Thoracoscopic Surgery (VATS) exhibits positive outcomes in treating stage I and II pleural empyema patients who incurred severe comorbidities.Keywords: pleural empyema, video-assisted thoracoscopic surgery, pus drainage